Occurrence of IGG antibodies anti-TOXOPLASMA GONDII and NEOSPORA CANINUM in cattle raised in family agricultural properties in Realeza, Parana, Brazil - Favero, Adriano; Arantes Pinto, Vanessa; Santos Alencar, Gabriela; Knorst Bellon, Amanda; Lays Petry, Alexandra; da Costa Freitas, Wagner Luiz; Antônio Mathias, Luis; da Costa Freitas, Fagner Luiz (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
This cross-sectional study evaluates the presence of antibodies against Neospora caninum and Toxoplasma gondii in cattle raised in Realeza, PR. There was a seroprevalence of N. caninum and T. gondii of 87.5% and 67.9%, respectively in the properties assessed. The frequencies of T. gondii and N. caninum in the animals were 41.1% and 55.1%, respectively. The studied coccidia are widely distributed in dairy cows reared on family farms in the municipality of Realeza, PR. Sanitary control for reproductive diseases must be adopted to prevent miscarriages and the economic damage caused by the disease. Future studies should be performed to investigate how widespread these pathogens are in cattle herds in southwestern Parana. KEYWORDS: Toxoplasmosis; neosporosis; Neospora caninum; Toxoplasma gondii; serology, Bos taurus.